2013
DOI: 10.3389/fmicb.2013.00397
|View full text |Cite
|
Sign up to set email alerts
|

Changes of cell growth and magnetosome biomineralization in Magnetospirillum magneticum AMB-1 after ultraviolet-B irradiation

Abstract: Effects of ultraviolet radiation on microorganisms are of great interest in field of microbiology and planetary sciences. In the present study, we used Magnetospirillum magneticum AMB-1 as a model organism to examine the influence of ultraviolet-B (UV-B) radiation on cell growth and magnetite biomineralization of magnetotactic bacteria (MTB). Live AMB-1 cells were exposed to UV-B radiation for 60, 300 and 900 s, which correspond to radiation doses of 120 J/m2, 600 J/m2, and 1800 J/m2, respectively. After irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 87 publications
0
16
0
Order By: Relevance
“…Cp values were generated automatically using the Abs Quant/2nd Derivative Max program of the LightCycler 480 software. Relative expression levels of different genes were calculated by the 2 ‐ΔΔCp method (Wang et al, ). Data shown are means of three replicates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cp values were generated automatically using the Abs Quant/2nd Derivative Max program of the LightCycler 480 software. Relative expression levels of different genes were calculated by the 2 ‐ΔΔCp method (Wang et al, ). Data shown are means of three replicates.…”
Section: Resultsmentioning
confidence: 99%
“…In submerged culture of MSR‐1, relative dissolved oxygen concentration (dO 2 ) < 1% was required for magnetosome formation (Zhang et al ., ). Our study demonstrated coordination, co‐dependence and balance of oxygen and iron metabolism gene activity in MSR‐1 during magnetosome synthesis, and suggested that oxygen level affects expression of iron metabolism genes because of coupling between the two metabolic pathways (Wang et al ., ). Questions remaining to be answered include: (i) How many genes are involved in the process of magnetosome synthesis in MTB?…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, Wang et al . () found that AMB‐1 cells produce more magnetite crystals with large grain sizes and long chains after UV‐B irradiation. Our results are consistent with these findings.…”
Section: Discussionmentioning
confidence: 98%
“…They also discuss the potential of magnetosomes as biomarkers for ancient life and the role of MTB in iron cycling. The study by Wang et al (2013) focuses on the influence of ultraviolet-B radiation on Magnetospirillum magneticum strain AMB-1. The authors note that ultraviolet-B radiation could affect both cell growth and magnetite synthesis, and suggest that magnetosomes may have evolutionary benefits for the survival of MTB under extreme environments.…”
mentioning
confidence: 99%